2020
DOI: 10.1093/sleep/zsaa140
|View full text |Cite
|
Sign up to set email alerts
|

Associations of loneliness and social isolation with actigraph and self-reported sleep quality in a national sample of older adults

Abstract: Study Objectives To examine associations of social isolation and loneliness with sleep in older adults, and whether associations differ for survey and actigraph sleep measures. Methods This study used data from The National Social Life, Health, and Aging Project (NSHAP), a nationally-representative study of community dwelling older adults born 1920-1947. A random one-third of participants in 2010/2011 were invited to particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 54 publications
1
36
1
Order By: Relevance
“…From the literature reviewed, in both older adults and adolescents, loneliness and social isolation have been associated with worse sleep quality, typically in the form of sleep fragmentation [ 47 , 48 , 49 , 50 , 51 , 52 ]. Poor sleep quality has also been linked with a higher risk of cognitive decline and poorer neurocognitive health [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…From the literature reviewed, in both older adults and adolescents, loneliness and social isolation have been associated with worse sleep quality, typically in the form of sleep fragmentation [ 47 , 48 , 49 , 50 , 51 , 52 ]. Poor sleep quality has also been linked with a higher risk of cognitive decline and poorer neurocognitive health [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have specified that flourishing social relationships through social support 17,18 ) , and reduced social isolation 19,20 ) and loneliness 19 ) can improve sleep quality. Our results also corroborated this association in terms of social frailty, substantiating previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Rich social relationships improve mental health through stress-buffering, regularizing life rhythms, and promoting physical activities by meeting friends and going out, which in turn enhances sleep quality 17 ) . Several cross-sectional studies have shown that high social support is associated with good sleep quality 17,18) while social isolation and loneliness hamper the quality of sleep 19) . Moreover, in a longitudinal study, social isolation predicted poor sleep quality 20) , suggesting the possibility that the quality of sleep among older adults is hindered by social vulnerability.…”
mentioning
confidence: 99%
“…Greater social integration may also help to lessen the impact of negative psychological states that disturb sleep, such as stress (12,13), loneliness (14), and depression (15). Indeed, previous investigations have reported that greater social integration is associated with longer sleep duration, better sleep continuity, and greater regularity in sleep timing (16,17). Biobehavioral sleep characteristics may also be associated with patterns of nocturnal BP dipping via influences on inflammatory, autonomic, and metabolic pathways (18).…”
Section: Possible Indirect Effectsmentioning
confidence: 99%